Determination of heavy metals in almagel and almagel-a preparations by anodic inversion voltammetry - Slepchenko G. B. Galina Borisovna; Zakharova E. A. Elsa Arminana; Kaminskaya O. V.; Blinnikova A. A.; Emel'yanova L. A. (2002, 2002)
Title screen